(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The article is devoted to the problem of understanding the impact of bureaucratic documentation (informational, instructional, circular letters and others) on the communication of literary organizations (from the center to local organizations). The VAPP, which separated from it in May 1928, was taken as a literary institution, and the Organizing Committee of the Union of Soviet Writers, formed by the Resolution of the Organizing Bureau of the Central Committee of the CPSU(b) dated May 7, 1932 “On measures to implement the resolution of the Politburo of the Central Committee of the CPSU (b) “On the Restructuring of literary and Artistic Organizations”, the Organizing Committee of the Union of Soviet Writers.